The Consequences of Prisoners' Micro‐Resistance. Issue 1 (11th November 2015) - Rubin, Ashley T.
Abstract : For more than twenty years, scholars have called for greater attention to the consequences of micro‐resistance to legality. Using archival data from Philadelphia's Eastern State Penitentiary (1829–1875), I examine the consequences of noncompliant prisoner behavior. I find that prisoners' noncompliance often entailed substantial costs to prisoners, particularly in comparison to the substantial benefits of complying with the prison regime. Despite its cost to prisoners, noncompliance did not have a single set of uniformly negative consequences for the prison regime. In fact, some forms of noncompliance may have actually protected the prison's reputation. Prison administrators, external allies, and critics used episodes of noncompliance for their own goals and to reinforce their preexisting claims about the propriety of competing prison designs, yielding this variable significance of noncompliance. As this study illustrates, connecting prisoner misconduct to power dynamics in the broader field produces a fuller understanding of micro‐resistance's consequences.